Posterior Tibial Subchondral Bone and Meniscal Slope Correlate with In Vivo Internal Tibial Rotation. Issue 7 (21st July 2017) - Herbst, Elmar; Gale, Tom; Nagai, Kanto; Tashiro, Yasutaka; Irrgang, James J.; Anderst, William; Tashman, Scott; Fu, Freddie H.
Objectives: Increased posterior tibial slope (PTS) results in an anteriorly directed force on the knee and is associated with a high-grade pivot shift. However, all published articles on this topic draw conclusions based on static measurements, while no study investigated the role of the PTS and posterior meniscal slope (PMS) on in vivo knee kinematics. Therefore, the objective of this study was to correlate the lateral and medial PTS and PMS with in vivo anterior tibial translation (ATT) and internal tibial rotation during level walking and downhill running on both the ACL reconstructed and healthy knees six months after index surgery. It was hypothesized that an increased lateral PTS and lateral PMS are associated with increased ATT and internal tibial rotation. Methods: Forty-two individuals (twenty-six males; mean age 21.2 ± 6.9 years) who underwent unilateral ACL reconstruction were included in this study. Morphologic parameters were measured on 3T magnetic resonance images (MRI) using the 3D DESS sequence on the ACL reconstructed and healthy contralateral knee. Lateral and medial PTS and PMS were measured according to the method described by Hudek et al. Briefly, the tibial shaft axis was determined by connecting the centroids of two circles fitting the tibial shaft on the central sagittal MRI slice. The PTS and PMS were determined by the angle between the tibial shaft axis and the line connecting the two most proximal anterior and posterior subchondral bone and meniscal points in the center of each joint compartment. Three-dimensional in vivo kinematics data were acquired using dynamic stereo X-ray during level walking (1.3 m/s) at 100 Hz and downhill running (3.0 m/s, 10° slope) at 150 Hz, six months after unilateral ACL reconstruction. Correlations between bone morphology and dynamic kinematics were evaluated using Spearman´s Rho. The significance level was set at p < .05. Results: In ACL intact knees, ATT did not correlate significantly with PTS and PMS (all p ≥ .264; Table 1). Internal tibial rotation was associated with higher posterior slopes in the lateral knee compartment. Larger differences between lateral and medial PTS and PMS were significantly correlated with increased internal tibial rotation (all ≤ .010), while medial PTS and PMS did not correlate with tibial rotation (all p ≥ .457). In ACL reconstructed knees ATT was positively correlated with an increased lateral PMS during level walking (p = .016). ACL reconstructed knees were found to have greater internal tibial rotation with larger lateral compartment slopes as well as with larger lateral-medial differences for PTS and PMS during level walking (all p ≤ .035). Conclusion: The most important finding of the present study is that both lateral PTS and PMS are related to dynamic, functional in vivo kinematics, especially internal tibial rotation. ATT was only associated with lateral PMS in ACL reconstructed knees. Taking into account the results of the present study, the lateral PTS and PMS and the slope differences between the lateral and medial joint compartment may contribute to internal rotation when an ACL injury occurs. However, the analyzed movement was a straight-ahead walk and run without any cutting or pivoting maneuvers commonly related to ACL tears. In such motion patterns, the correlations may be even stronger compared to the results of this study. However, this novel study is the first to assess the relationship between articulating surface morphology and in vivo functional movement.